Economic Theories on Social Entrepreneurship - Hamid, Zarinah; Zhang, Hengchao (Kulliyyah of Economics and Management Sciences, IIUM, 2021)
This chapter discussed the economic theories on social entrepreneurship. From economic perspectives, social entrepreneurship has developed as an economic field of studies in the late 1990s when the researchers argued on the economic role of social entrepreneurship.